2022
DOI: 10.26434/chemrxiv-2022-dst89
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery and Characterization of a Terpene Biosynthetic Pathway featuring a Norbornene-forming Diels-Alderase

Abstract: Pericyclases, enzymes that catalyze pericyclic reactions, form an expanding family of enzymes that have biocatalytic utility. Despite the increasing number of pericyclases discovered, the Diels-Alder (DA) cyclization between a cyclopentadiene and an olefinic dienophile to form norbornene, which is among the best-studied cycloadditions in synthetic chemistry, has surprisingly no enzymatic counterpart to date. Here we report the discovery of a pathway featuring a norbornene synthase SdnG for the biosynthesis of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…A relevant area of study is enzymatic reactions (e.g., Diels-Alderases), where interactions between various functional groups influence the rate and endo/exo selectivity of DAC reactions. [38][39][40][41] Practical and theoretical experiments have shown that the enzymatic reaction proceeds via an asynchronous Diels-Alder mechanism by changes to the structural and electronic properties of the transition state. 39,40 Therefore, a possible explanation for the variation in rate and endo/exo stereoselectivity of the DAC reactions between 1 and 2 in different buffers (Table 2) are interactions (e.g., H-bonding) between the functional groups on the buffering agents and the reactants that influence and favour the stabilisation of the endo transition-state.…”
Section: Papermentioning
confidence: 99%
“…A relevant area of study is enzymatic reactions (e.g., Diels-Alderases), where interactions between various functional groups influence the rate and endo/exo selectivity of DAC reactions. [38][39][40][41] Practical and theoretical experiments have shown that the enzymatic reaction proceeds via an asynchronous Diels-Alder mechanism by changes to the structural and electronic properties of the transition state. 39,40 Therefore, a possible explanation for the variation in rate and endo/exo stereoselectivity of the DAC reactions between 1 and 2 in different buffers (Table 2) are interactions (e.g., H-bonding) between the functional groups on the buffering agents and the reactants that influence and favour the stabilisation of the endo transition-state.…”
Section: Papermentioning
confidence: 99%